DETERMINAN KEPATUHAN PADA KETENTUAN PENGUNGKAPAN WAJIB LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Kabupaten/Kota Di Provinsi Nusa Tenggara Barat) - Mira Feriyanti; H. Hermanto; Ni Ketut Suransi (Universitas Trunojoyo Madura, 2015)
This research aimed to analyze the determinants of compliance toward the provisions of mandatory disclosure of financial statements of local governments (LKPD) throughout districts / cities in West Nusa Tenggara Province which consists of eight regencies and two Cities. This research is quantitative in nature. The data used is secondary data sourced from Audit Reports on LKPD by the Supreme Audit Agency (BPK), overview of the results of BPK and data of the Central Bureau of Statistics for the period of 2011 to 2013. Data were collected by using documentation technique and literature. The analytical method used is panel data regression using the software eviews 8. The results of the research indicate that the wealth of the region, the level of dependence, the age of administrative local government, the number of legislators, total SKPD and deviation rate based BPK audit results have significant influence on the level of disclosure of financial statements of local governments, while the population and the number of audit findings do not have a significant influence on the level of disclosure LKPD .